Modal Sosial Perawat Perempuan Pada Masa Pandemi Covid-19 di RSUD Kota Bogor - Afifah Bidayaturrohmah (NUANSA: Jurnal Penelitian Ilmu Sosial dan Keagamaan Islam, 2023)
The purpose of writing this article is to explain the social capital obtained by female nurses during handling in the Covid-19 room. The spread of the Covid-19 virus has had a severe impact in the city of Bogor with a population density that is mostly mobilised in DKI Jakarta, thus triggering an increase in the spread of the Covid-19 virus. The recent Covid-19 pandemic strengthens the evidence that cities are vulnerable to disease, even the Covid-19 pandemic has become a big problem for female nurses, where they face a lot of pressure, anxiety, and stress while on duty in the Covid-19 room. Nurses need social capital as a form of interpersonal relationships among colleagues, superiors and faith in Allah SWT that can reduce workload while on duty in the Covid-19 treatment room. The methodology used in this study is a qualitative approach with a case study research type. Data sources were obtained through observation and interviews using purposive sampling with specialised snowball sampling through semi-structured interviews with four informants. Some characteristics of the informants involved in the study are: female aged approximately 35 years; nurse with permanent employee status; married status; and served in the special treatment room for Covid-19 virus patients. The findings of this study show that social capital owned by female nurses has three components, namely: bonding, bridging, and linking. In addition, religious values are also important as social capital which is divided into three aspects, namely: Tauhid, Patience, Tawakal, and Ikhlas. These four aspects can play an important role as a form of spiritual support to Allah SWT and as a self-strengthener while on duty in the Covid-19 treatment room at Bogor City Hospital. (Tujuan penulisan artikel ini adalah untuk menjelaskan modal sosial yang diperoleh perawat perempuan selama melakukan penanganan di ruang Covid-19. Penyebaran virus Covid-19 memberi dampak cukup parah di Kota Bogor dengan kepadatan penduduk yang sebagian besar bermobilitas di DKI Jakarta, sehingga memicu peningkatan penyebaran virus Covid-19. Pandemi Covid-19 belakangan ini memperkuat bukti bahwa kota rentan menjadi sasaran penyakit, bahkan pandemi Covid-19 telah menjadi masalah besar bagi para perawat perempuan, di mana mereka menghadapi banyak tekanan, kecemasan, dan stres selama bertugas di ruang Covid-19. Perawat membutuhkan modal sosial sebagai bentuk hubungan interpersonal di antara rekan kerja, atasan serta keyakinan kepada Allah SWT yang dapat mengurangi beban kerja selama bertugas di ruang perawatan Covid-19. Metodologi yang digunakan di dalam studi ini berada dalam pendekatan kualitatif dengan jenis penelitian studi kasus. Sumber data diperoleh melalui observasi dan wawancara secara purposive sampling dengan secara khusus menggunakan snowball sampling melalui wawancara semi-terstruktur kepada empat orang informan. Beberapa karakteristik informan yang dilibatkan di dalam penelitian yaitu: perempuan berusia kurang lebih 35 tahun; perawat berstatus pegawai tetap; status menikah; dan bertugas di ruang perawatan khusus pasien virus Covid-19. Temuan dari penelitian ini menunjukkan bahwa modal sosial yang dimiliki perawat perempuan memiliki tiga komponen, yaitu: bonding, bridging, dan linking. Selain itu, penting juga nilai agama sebagai modal sosial yang terbagi menjadi tiga aspek yaitu: Tauhid, Sabar, Tawakal, serta Ikhlas. Dari ke-empat aspek ini dapat berperan penting sebagai bentuk dukungan spiritual kepada Allah SWT dan sebagai penguat diri selama bertugas di ruang perawatan Covid-19 di RSUD Kota Bogor.)